Effectiveness of movement system impairment (MSI) based classification treatment on clinical outcomes among subjects with tibiofemoral hypomobility syndrome: A randomized controlled trial. - Paarthasarathy, K.; Soundararajan, K.; Antony Leo Asser, P.; Subbiah, K.; Chrysolyte, M. (Journal of Bodywork & Movement Therapies, 2025)
Movement impairment of the knee exists as a repetitive microtrauma from stress induced by altered knee movement or alignment in a specific direction. The movement system impairment approach provides a framework focused on correcting faulty movement patterns. There is a lack of literature on treatment for tibiofemoral hypomobility syndrome. The study aims to compare the effectiveness of movement system impairment-based treatment (MSI) and standard physical therapy care in subjects with tibiofemoral hypomobility syndrome. This randomized controlled trial initially screened ninety-eight participants for eligibility. Of these, sixty-six individuals diagnosed with tibiofemoral hypomobility syndrome were enrolled in this study. Following the baseline assessment, the participants were randomly allocated into the experimental or the control group. Physical performance, pain severity, knee mobility, and disability were evaluated for each patient at baseline and the end of 3rd week. The findings revealed a significant improvement in pain intensity, knee mobility, physical performance, and disability (<0.001) within both groups and between both groups (NPRS p-value <0.001, knee flexion p-value <0.001, knee extension p-value <0.001, KOOS p-value <0.001, sit-to-stand p-value <0.001) over three weeks. The MSI treatment model effectively treats subjects with tibiofemoral hypomobility syndrome and shows greater improvement than standard physical therapy care. These findings suggest that MSI-based treatment can contribute to global health efforts to minimize musculoskeletal conditions. Further studies to bring long-term follow-up and other physical performance outcomes. • Individual diagnosed with knee mobility deficits respond best to movement system impairment based diagnosis and treatment. • Movement System Impairment is based on identifying faulty movement/posture and prescribing exercise. • Treatment includes functional activities with specific instructions that may be better than the standard knee pain care.